Soft Photonic Crystals and Metamaterials - Timofeev, Ivan V.; Lee, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue on "Soft Photonic Crystals and Metamaterials" from Materials consists of 10 papers that highlight recent advances in a broad scope of optical-wavelength and sub-wavelength structures made of soft materials and particles. Soft matter shows plenty of unique and improved optical properties for deep scientific understanding, thereby promoting fabrication, characterization and device performance for potential photonic applications that include, but are not limited to, photovoltaic cells, photodetectors, light-emitting diodes, tunable microlasers, optical filters for biosensors, smart windows, virtual/augmented reality head-mounted elements, and high-speed spatial light modulators in glasses-free 3D displays.